Performance Evaluation In Family Physician: The Application of TOPSIS Multi-Criteria Decision Making Method - Engin Karaman (Alphanumeric Journal, 2015)

(untitled)
In this study, a performance analysis was carried out for the Family Practice application offered to the public by the Ministry of Health. Performance management serves a different purpose in public sectors which provide service in accordance with the principle of social benefit rather than of a profit-loss relationship in comparison with private sectors. Main objective herein is to improve the quality of the service offered to the public in terms of such criteria as efficacy, efficiency and productivity. In this study, the performances of 12 Family Practice units carrying on business in Alaca district of Corum in the months of the year of 2012 were converted into a single score indicating the general performance level with the help of the TOPSIS method among the Multi-Criteria Decision Making Techniques through the data of 8 criteria and such units were put into order in this regard and their performances were compared. At the end of the study, the proximity values (Ci) of the units according to the ideal solution they have received for 12 months were averaged and rated on a yearly basis. According to the average of Ci scores, the performances of 4 units were founded to be successful whereas 5 units displayed normal performance and the performance of 3 units were decided to be ineffective.